Peran Manajemen dalam Proses Identifikasi Risiko Pada Produk Cicil Emas di BSI KCP Banjarnegara - Yuwono, Cinanthya (Scimadly Publishing, 2025)
This article explores the risk management approaches adopted by BSI KCP Banjarnegara, a branch of Bank Syariah Indonesia located in Central Java, particularly in managing its gold installment financing program. As gold investment becomes increasingly popular, the bank must manage several risks, such as fluctuations in gold prices, creditworthiness of customers, operational issues, verifying the authenticity of gold, legal compliance, market dynamics, and adherence to Islamic financial principles. Based on 2023 data from the Financial Services Authority (OJK), there was an 18.5% national increase in gold installment transactions, highlighting the importance of strong risk management strategies. To mitigate these risks, BSI implements a comprehensive risk management system. This includes conducting 5C credit assessments, collaborating with trusted gold suppliers like Antam, and performing regular internal and external audits. In addition, BSI ensures compliance with Islamic law by using murabahah contracts in line with DSN-MUI (National Sharia Council of the Indonesian Ulema Council) guidelines. These practices help minimize financial risk while upholding values of fairness, transparency, and Islamic ethics. The article offers a fresh perspective by examining sharia-based risk management in gold financing, contrasting with conventional approaches. The insights shared can serve as guidance for other Islamic financial institutions looking to develop effective and sharia compliant financial products.